Controlling Subclinical Mastitis by Antibiotic Application during Dry Period of Dairy Cow - Imas Sri Nurhayati; E Martindah (Indonesian Center for Animal Research and Development, 2015)
Prevention of mastitis is essential, as one of the efforts to control disease in dairy cow. Dry period has implications to understand the mastitis and its control strategies. The udder is very susceptible to be infected both at the beginning and towards the end of dry period. This is linked to physiological changes in udder. Treatment with antibiotics during the dry period can reduce new infection about 82% and has several advantages. The success rate of subclinical mastitis treatment is much higher (80-90%) compared to the treatment during lactation (30-40%); the doses of antibiotic can be higher and safer, due to its retention time in udder becomes longer; the risk of antibiotic contamination in milk can be avoided because the udder is not milked. Antibiotic application during dry period is the best way to treat subclinical and chronic mastitis. Treatment during dry period is a specific mastitis control for intramammary infection to avoid economic losses. Key words: Antibiotic, dry period, subclinical mastitis